ECTHR_COMMITTEE 21594/05 vom 28. Mai 2014 , AFFAIRE YELISEYEV c. RUSSIE - Ecthr Committee (2014)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure civile;Article 6-1 - Procès équitable); Violation: 6;6-1